2019
DOI: 10.1021/acssuschemeng.9b00851
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Absorption of SO2 by Deep Eutectic Solvents Formed by Biobased Aprotic Organic Compound Succinonitrile and 1-Ethyl-3-methylimidazolium Chloride

Abstract: We report that deep eutectic solvents can be formed by biobased aprotic organic compound succinonitrile (SN) functionalized as the hydrogen bond donor with solid ionic liquid 1-ethyl-3-methylimidazolium chloride ([Emim]­[Cl]) or 1-ethyl-3-methylimidazolium hexafluorophosphate ([Emim]­[PF6]). The results suggested the formation of intermolecular hydrogen bonds between the anions of imidazolium salts and the C–H hydrogen of SN. Moreover, the deep eutectic solvent [Emim]­[Cl]-SN(1:1) exhibited an attractive SO2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Moreover, the physiochemical properties of ILs and DESs can be easily tuned by manufacturing the structures and/or compositions of ILs and DESs. Therefore, ILs and DESs are regarded as the next-generation solvents for gas separation, , and there have been enormous studies dedicated to the development of ILs- and DESs-based solvents for green and efficient capture of CO 2 , SO 2 , and H 2 S. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the physiochemical properties of ILs and DESs can be easily tuned by manufacturing the structures and/or compositions of ILs and DESs. Therefore, ILs and DESs are regarded as the next-generation solvents for gas separation, , and there have been enormous studies dedicated to the development of ILs- and DESs-based solvents for green and efficient capture of CO 2 , SO 2 , and H 2 S. …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that imidazolium-based ILs exhibited considerable SO 2 absorption capacity. Therefore, Yang et al [41][42][43] designed a series of EmimCl-based DESs, including EmimCl:EG DES (1:1), EmimCl:triethylene glycol(TEG) DES (1:1), and EmimCl:succinonitrile (SN) DES (1:1), for efficient SO 2 capture and obtained the corresponding absorption capacity of 1.03, 0.91, and 1.13 g SO 2 /g DES, respectively, at 293.15 K and 101 kPa. It showed that the efficiency of imidazolium cation is better than that of ammonium.…”
Section: Imidazolium-based Dessmentioning
confidence: 99%
“…Yang et al [ 106 ] investigated the effect of HBD of DESs [EMIMC/EG (1:1), EMIMC:TEG (1:1), and EMIMC:SNT (1:1)] on the solubility of SO 2 . The effect of HBD was ordered as SNT > EG > TEG for SO 2 capture.…”
Section: Capture Of Acidic Gasesmentioning
confidence: 99%
“…SO 2 capture via DESs decreased linearly with increasing temperature. Yang et al also reported that the absorption capacity of SO 2 using EMIMC/EG, EMIMC/TEG, and EMIMC/SNT decreased with increasing temperature [ 104 , 105 , 106 ].…”
Section: Capture Of Acidic Gasesmentioning
confidence: 99%